1981
DOI: 10.1161/01.cir.63.6.1371
|View full text |Cite
|
Sign up to set email alerts
|

The transition to ventricular fibrillation induced by reperfusion after acute ischemia in the dog: a period of organized epicardial activation.

Abstract: Ventricular fibrillation was induced in eight of 10 open-chest dogs by reperfusion after a 15-minute occlusion of the proximal circumflex coronary artery. Simultaneous recordings were made from 27 epicardial electrodes spaced over both ventricles. Analysis of the initial 1.5--2.5 seconds of the transition from sinus rhythm or ventricular tachycardia to fibrillation revealed that ventricular activation occurred in an orderly, rapidly repeating sequence in all hearts. Each activation from arose near the border o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

1987
1987
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(35 citation statements)
references
References 32 publications
2
29
0
4
Order By: Relevance
“…Previously, Janse et al (6) have shown that, whereas complete and incomplete reentrant waveforms were seen during transition of reperfusion VT to VF, no evidence of reentry was seen during the initiation of VT in isolated canine and porcine hearts. Ideker et al (5) suggested that during transition of reperfusion VT to VF the complexes were initiated by a focal source in the ischemic border zone in the dog. These studies were somewhat limited in that the number of recording sites did not allow for exact delineation of the mechanism of the arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Janse et al (6) have shown that, whereas complete and incomplete reentrant waveforms were seen during transition of reperfusion VT to VF, no evidence of reentry was seen during the initiation of VT in isolated canine and porcine hearts. Ideker et al (5) suggested that during transition of reperfusion VT to VF the complexes were initiated by a focal source in the ischemic border zone in the dog. These studies were somewhat limited in that the number of recording sites did not allow for exact delineation of the mechanism of the arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…It has indeed been found that in the initial phase of reperfusion-induced VF ͑i.e., when blood flow to an ischemic region is suddenly restored͒, the normal myocardium is rapidly excited by orderly wave fronts emerging from the reperfused myocardium. 32 In Fig. 2 epicardial activation maps of the first beats of VF, occurring spontaneously after 5 min of ischemia, are shown.…”
Section: Is the Purkinje System Necessary For The Transition Of Ventrmentioning
confidence: 99%
“…Experimental studies are generally restricted to mapping electrical activity on the ventricular surfaces [7,[10][11][12], and major advances have been achieved through the simultaneous mapping of endocardial and epicardial activity in a ventricular slice preparation [6] and the panoramic mapping of activity over the surface of the entire heart [13,14]. Theory, experiments and clinical studies all lead to a need to visualise, within the ventricular wall, the pattern of events occurring during VF.…”
mentioning
confidence: 99%